A three-country survey of public attitudes towards the use of rationing criteria to set healthcare priorities between patients. Issue 4 (12th November 2018) - Pinho, Micaela; Pinto Borges, Ana
Abstract : Purpose: The purpose of this study is to explore and compare citizens' attitudes in Portugal, Bulgaria and Croatia towards rationing criteria that should support an explicit priority setting process at the micro level. Design/methodology/approach: Preferences were collected through an online questionnaire containing 14 statements concerning lottery, economic and person-based priority criteria. Respondents indicated their level of agreement with each criterion. Non-parametric tests were applied to compare the levels of agreement among 355, 298 and 243 Portuguese, Bulgarian and Croatian respondents, respectively. Findings: The three groups of respondents appear to be concerned with both a fair and efficient allocation of resources. The severity of health conditions and patient's age were the criteria most accepted by the respondents. This study suggests that Portuguese, Bulgarian and Croatian respondents have similar social values concerning patient prioritization, although the Portuguese adhere slightly more to efficiency criteria and less to person-based and lottery criteria than Bulgarian and Croatian respondents. Practical implications: A majority of respondents across the three countries report having opinion about the bedside rationing criteria. Portuguese, Bulgarian and Croatian respondents accept a combination of personal and economic criteria in patient's prioritization. Originality/value: This study represents the first attempt to compare citizen's opinions of three member states of the European Union. Paper type: Research paper